Direction of escape in reindeer - Baskin, Leonid M.; Skogland, Terje (Rangifer, 1997)
We tested the hypothesis that reindeer prefer to run uphill and upwind when escaping from man. Groups of wild and feral reindeer in Norway, Svalbard and on Wrangel Island were approached and their behaviour and direction of escape were recorded. Two stages of interaction with man were studied: first flight and final withdrawal. First flights proved to be away from man, upwind and uphill. Most final withdrawals were in the direction reindeer were moving when first observed.